Indium oxide-bismuth oxide composite oxide with (111) crystal face and preparation method thereof

By preparing indium oxide-bismuth oxide composite oxide with (111) crystal surface in CO2 electroreduction reaction, the problems of high overpotential and unsatisfactory stability in the reaction were solved, and the effect of efficient preparation of formic acid was achieved.

CN119608147AActive Publication Date: 2025-03-14NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510148308.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing indium-based catalysts have high overpotential and poor stability in CO2 electroreduction reactions, which limits their application in the preparation of formic acid reactions.

Method used

By using ethylene glycol and water as the mixed solvent, indium nitrate and bismuth nitrate as the indium and bismuth sources, urea as the alkali source, and heating reaction after ultrasonic dissolution, an indium oxide-bismuth oxide composite oxide with (111) crystal surface was prepared.

Benefits of technology

This catalyst showed high selectivity and high Faraday efficiency in CO2 electroreduction reaction, and the Faraday efficiency of formic acid reached more than 90%, which significantly improved the catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608147A_ABST
    Figure CN119608147A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalyst preparation, and particularly discloses an indium oxide-bismuth oxide composite oxide with a (111) crystal face and a preparation method thereof.The preparation method comprises the steps that indium nitrate, bismuth nitrate and urea are dissolved in a mixed solvent containing ethylene glycol and water, a heating reaction is conducted, and a reaction solution containing the indium oxide-bismuth oxide composite oxide with the (111) crystal face is obtained; in the mixed solvent, the volume ratio of water is 3%-10%. The method provided by the invention has the advantages that the preparation process is simple, the repeatability is good, and the carrier-free composite oxide catalyst can be conveniently synthesized in batches, in the process of preparing formic acid through reduction of the catalyst, the selectivity of formic acid is high, the Faraday efficiency of CO2 electroreduction of formic acid is about 90%, and the catalyst is expected to be widely applied in the field of electrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst preparation, and in particular to an indium oxide-bismuth oxide composite oxide having a (111) crystal plane and a preparation method thereof. Background Art

[0002] This section merely provides background information related to the present disclosure and is not necessarily prior art.

[0003] As the global climate change problem becomes increasingly serious, CO2 emission reduction and resource utilization have become one of the important issues that need to be urgently addressed in today's society. CO2 electroreduction (CO2RR) technology has attracted much attention because it converts CO2 into high-value-added chemicals and fuels, such as formic acid and methanol, under mild conditions. Formic acid is not only an important chemical raw material, but also can be used as a hydrogen source for fuel cells, and has broad application prospects. In recent years, metallic indium, as a low-toxic p-group metal, has attracted widespread attention from researchers because of its high overpotential for hydrogen evolution reaction, its ability to highly selectively reduce CO2 to formic acid, and its ability to achieve a high current density. However, the high overpotential and unsatisfactory stability of indium-based catalysts themselves limit their further development. The construction of bimetallic oxides, stabilizing intermediates and inhibiting hydrogen evolution reactions, thereby improving the activity of CO2 electroreduction reactions.

[0004] In recent years, composite oxides of indium and bismuth have shown good application prospects in CO2 electroreduction due to their different surface electronic structures and diverse active sites. The synergistic effect of indium and bismuth can effectively stabilize CO2 reduction intermediates, inhibit hydrogen evolution reaction, and thus improve the yield and Faraday efficiency of formic acid. However, current research focuses on the simple composite of indium oxide and bismuth oxide (X. Chen, Journal of Colloid and Interface Science, 2025,678; CN 109939670 A), while ignoring the profound influence of its crystal face structure on catalytic performance. Crystal face regulation technology can selectively expose specific crystal faces to increase the density of active centers on the catalyst surface, thereby enhancing its adsorption, activation and electron transfer process for CO2 molecules, thereby significantly improving the reaction activity and selectivity of the catalyst. Therefore, it is of great research significance and application value to optimize and improve the composite oxide materials of indium oxide and bismuth oxide based on the crystal face selection strategy to improve its performance in the CO2 electroreduction reaction to produce formic acid. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide an indium oxide-bismuth oxide composite oxide with a (111) crystal plane and a preparation method thereof, and its application in the preparation of formic acid by CO2 electroreduction in view of the shortcomings of the prior art.

[0006] In order to solve the above technical problems, the present invention discloses the following technical solutions: In a first aspect, the present invention discloses an indium oxide-bismuth oxide composite oxide having a (111) crystal plane and a preparation method thereof.

[0007] In the preparation method, ethylene glycol and water are used as a mixed solvent, indium nitrate and bismuth nitrate are used as indium and bismuth sources respectively, and urea is used as an alkali source.

[0008] Specifically, the preparation method of the indium oxide-bismuth oxide composite oxide having a (111) crystal face comprises ultrasonically dissolving indium nitrate, bismuth nitrate and urea in a mixed solvent containing ethylene glycol and water, mixing them evenly, heating them for reaction, and obtaining a reaction solution containing the indium oxide-bismuth oxide composite oxide having a (111) crystal face; the obtained reaction solution is cooled to room temperature, washed with deionized water and anhydrous ethanol in sequence, centrifuged, dried, and calcined at 300-600° C. for 2-5 hours to obtain the indium oxide-bismuth oxide composite oxide having a (111) crystal face.

[0009] Wherein, the volume ratio of water in the mixed solvent is 3% to 10%, such as 5%, 7%, and 9%.

[0010] Wherein, the molar volume ratio of the indium nitrate to the mixed solution is 0.2-2 mmol:29-30 mL, such as 0.5 mmol:29-30 mL, 1.5 mmol:29-30 mL.

[0011] Wherein, the molar ratio of indium nitrate to bismuth nitrate is 1:3~3:1.

[0012] Wherein, the ratio of the total molar amount of the indium nitrate and the bismuth nitrate to the molar amount of urea is 1:5-7, such as 1:6.

[0013] Wherein, the temperature of the heating reaction is 120~130℃.

[0014] Wherein, the heating reaction time is 16 to 18 hours.

[0015] In a second aspect, the present invention discloses the use of the above-mentioned indium oxide-bismuth oxide composite oxide having a (111) crystal plane as a catalyst in catalyzing the electroreduction of CO2 to prepare formic acid.

[0016] Among them, the potential for preparing formic acid by electroreduction is -0.8~-1.4.

[0017] Wherein, the catalyst loading is 0.5-1.5 mg / cm 2 , such as 1 mg / cm 2 .

[0018] Beneficial effects: 1. The method provided by the present invention has the advantages of simple preparation process, good repeatability, and convenient batch synthesis of composite oxide catalysts without carriers, and the catalyst has high selectivity for formic acid in the process of reducing and preparing formic acid.

[0019] 2. The present invention prepares a composite oxide of indium oxide and bismuth oxide with a (111) crystal plane, and the Faraday efficiency of CO2 electroreduction of formic acid is about 90%. The catalyst is expected to be widely used in the field of electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0021] Figure 1 This is the X-ray diffraction pattern of the indium oxide-bismuth oxide catalyst prepared in Example 1 of the present invention.

[0022] Figure 2 The figures are scanning electron microscope images (a) and transmission electron microscope images (b) of the indium oxide-bismuth oxide catalyst prepared in Example 1 of the present invention.

[0023] Figure 3 It is a formic acid Faraday efficiency diagram of the indium oxide-bismuth oxide catalyst prepared in the present invention.

[0024] Figure 4 This is the X-ray diffraction pattern of the indium oxide-bismuth oxide catalyst prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0025] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0026] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0027] The following embodiment provides a method for preparing an indium oxide-bismuth oxide composite oxide having a (111) crystal face. The method can use a simple hydrothermal process within a wide range of the molar ratio of indium oxide to bismuth oxide to rapidly and massively synthesize a CO2 electroreduction reaction catalyst having a (111) crystal face, good dispersibility, high repeatability, and high selectivity.

[0028] Example 1 28 mL of ethylene glycol and 1 mL of deionized water were mixed to form a mixed solvent, and then 1.0 mmol of indium nitrate, 1.0 mmol of bismuth nitrate and 0.70 g of urea were added, and ultrasonic treatment was performed until the mixture was completely dissolved. The mixture was stirred for 1 hour until the mixture was completely uniform. The obtained mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, placed in a forced air drying oven, and hydrothermally reacted at 120 ° C for 17 hours. Then it was cooled naturally to room temperature, and the obtained precipitate was washed with deionized water and anhydrous ethanol in turn, centrifuged, and dried in an oven at 60 ° C for 12 hours to obtain a precursor product. The precursor product was transferred to a tube furnace and calcined in air at 600 ° C for 2 hours to obtain an indium oxide-bismuth oxide composite oxide with a (111) crystal face.

[0029] Evaluation of CO2 electroreduction reaction: 10 mg of indium oxide-bismuth oxide composite oxide catalyst with (111) crystal plane was added to 20 uL of 5% Nafion solution and 1000 uL of isopropanol to prepare ink solution. Ultrasonic dispersion was performed for 30 minutes. 25 uL of ink solution was dispersed in 0.25 cm 2 The catalyst loading on the carbon paper was about 1 mg / cm 2 , dried under infrared lamp for 10min. Tested in H-type electrolytic cell three-electrode system, CO2 flow rate was 20 sccm, 0.1 M KHCO3 was electrolyte, electrolysis was 60min, gas phase products H2 and CO were detected by gas chromatography, liquid phase products were detected by liquid nuclear magnetic resonance, and voltage was applied by electrochemical workstation during the whole electrochemical reaction process and current-time curve was recorded.

[0030] The X-ray diffraction spectrum of the indium oxide-bismuth oxide composite oxide with (111) crystal plane is shown in Figure 1 The positions and intensities of the diffraction peaks are consistent with those of the indium oxide standard card (JCPDS 06-0416) and the bismuth oxide standard card (JCPDS 27-0050). Figure 2 (a) shows that the size and morphology of indium oxide-bismuth oxide are uniform particles. High-magnification transmission electron microscopy image is shown in Figure 2 (b) It can also be confirmed that the main exposed surface is the (111) crystal plane.

[0031] The indium oxide-bismuth oxide catalyst was used for the CO2 electroreduction reaction. The catalytic results are shown in Figure 3 In Example 1, under a wide potential range, the product is formic acid, and its Faradaic efficiency exceeds 90%.

[0032] Example 2 Mix 29 mL of ethylene glycol and 1 mL of deionized water to form a mixed solvent, then add 0.5 mmol of indium nitrate, 1.5 mmol of bismuth nitrate and 0.65 g of urea, ultrasonicate until completely dissolved, and stir thoroughly for 1 hour until the mixed solution is completely uniform. The obtained mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, placed in a forced air drying oven, and hydrothermally reacted at 130°C for 16 hours. Then cool naturally to room temperature, wash the obtained precipitate with deionized water and anhydrous ethanol in turn, centrifuge, and dry in an oven at 60°C for 12 hours to obtain a precursor product. The precursor product was transferred to a tubular furnace and calcined in air at 600°C for 2 hours to obtain an indium oxide-bismuth oxide catalyst. The X-ray diffraction pattern of the indium oxide-bismuth oxide catalyst is shown in Figure 4 , the proportion of (111) crystal plane decreases, and the Faraday efficiency of CO2 electroreduction to formic acid is shown in Figure 3 Example 2, about 80%.

[0033] Example 3 Mix 28 mL of ethylene glycol and 1 mL of deionized water to form a mixed solvent, then add 1.5 mmol of indium nitrate, 0.5 mmol of bismuth nitrate and 0.75 g of urea, ultrasonicate until completely dissolved, and stir thoroughly for 1 hour until the mixed solution is completely uniform. The obtained mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, placed in a forced air drying oven, and hydrothermally reacted at 130°C for 18 hours. Then it was naturally cooled to room temperature, and the obtained precipitate was washed with deionized water and anhydrous ethanol in turn, centrifuged, and dried in an oven at 60°C for 12 hours to obtain a precursor product. The precursor product was transferred to a tubular furnace and calcined in air at 600°C for 2 hours to obtain an indium oxide-bismuth oxide composite oxide with a (111) crystal face. Its Faraday efficiency for CO2 electroreduction to formic acid is shown in Figure 3 In Example 3, at a potential of -1.0 to -1.1 V, the Faradaic efficiency reaches 90%, and the potential window thereafter remains at about 80%.

[0034] Comparative Example 1 Mix 27 mL of ethylene glycol and 3 mL of deionized water to form a mixed solvent, then add 1 mmol of indium nitrate and 0.40 g of urea, ultrasonicate until completely dissolved, and stir thoroughly for 1 hour until the mixed solution is completely uniform. The resulting mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, placed in a forced air drying oven, and hydrothermally reacted at 130°C for 18 hours. Then cool naturally to room temperature, wash the resulting precipitate with deionized water and anhydrous ethanol in turn, centrifuge, and dry in an oven at 60°C for 12 hours to obtain a precursor product. The precursor product was transferred to a tubular furnace and calcined in air at 600°C for 5 hours to obtain indium oxide with a (111) crystal face. Its Faraday efficiency for CO2 electroreduction to formic acid is shown in Figure 3 In comparative example 1, the onset potential was slightly increased, and the Faradaic efficiency of formic acid was between 70% and 80%.

[0035] Comparative Example 2 Mix 29 mL of ethylene glycol and 1 mL of deionized water to form a mixed solvent, then add 1 mmol of bismuth nitrate and 0.30 g of urea, ultrasonicate until completely dissolved, and stir thoroughly for 1 hour until the mixed solution is completely uniform. The resulting mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, placed in a forced air drying oven, and hydrothermally reacted at 120°C for 17 hours. Then cool naturally to room temperature, wash the resulting precipitate with deionized water and anhydrous ethanol in turn, centrifuge, and dry in an oven at 60°C for 12 hours to obtain a precursor product. The precursor product was transferred to a tubular furnace and calcined in air at 600°C for 2 hours to obtain bismuth oxide. Its Faraday efficiency for CO2 electroreduction to formic acid is shown in Figure 3 In comparative example 2, the Faradaic efficiency of formic acid is between 70% and 80%.

[0036] Comparative Example 3 Same as Example 1, except that 28 mL of ethylene glycol and 1 mL of deionized water were replaced with 28 mL of ethylene glycol, and indium oxide-bismuth oxide composite oxide could not be synthesized.

[0037] Comparative Example 4 The same as Example 1, except that 28 mL of ethylene glycol and 1 mL of deionized water were replaced with 5 mL of ethylene glycol and 24 mL of water. As a result, the Faradaic efficiency of formic acid was only about 60%.

[0038] It can be seen that the present invention provides a nanomaterial with crystal face selectivity, and in particular designs an indium oxide-bismuth oxide composite oxide with a (111) crystal face, which has high selectivity for formic acid. Specifically, the present invention does not require any template or structure directing agent. By using an ethylene glycol-water mixed solvent thermal method, the ratio of urea to metal precursor salt, hydrothermal temperature and synthesis time can be adjusted to obtain an indium oxide-bismuth oxide composite oxide with a (111) crystal face. The synthesis method has the advantages of simple process, low cost, relatively uniform product morphology and size, large-scale synthesis and good repeatability; the indium oxide and bismuth oxide composite oxide synthesized by this method has high selectivity in the CO2 electroreduction reaction, and the Faraday efficiency of the product formic acid is measured to be above 80% in an H-type electrolytic cell.

[0039] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an indium oxide-bismuth oxide composite oxide having a (111) crystal plane, characterized in that: Indium nitrate, bismuth nitrate and urea are dissolved in a mixed solvent containing ethylene glycol and water, and heated for reaction to obtain a reaction solution containing the indium oxide-bismuth oxide composite oxide having a (111) crystal face; in the mixed solvent, the volume ratio of water is 3% to 10%.

2. The method according to claim 1, characterized in that The molar ratio of indium nitrate to bismuth nitrate is 1:3 to 3:

1.

3. The method according to claim 1, characterized in that The ratio of the total molar amount of the indium nitrate and the bismuth nitrate to the molar amount of urea is 1:5-7.

4. The method according to claim 1, characterized in that The temperature of the heating reaction is 120-130°C.

5. The method according to claim 1, characterized in that The heating reaction time is 16 to 18 hours.

6. The method according to claim 1, characterized in that After the heating reaction is completed, the mixture is cooled, washed, dried and calcined to obtain an indium oxide-bismuth oxide composite oxide having a (111) crystal plane.

7. The method according to claim 6, characterized in that The calcination is carried out at 300-600° C. for 2-5 hours.

8. An indium oxide-bismuth oxide composite oxide having a (111) crystal plane prepared by the method according to any one of claims 1 to 7.

9. Use of the indium oxide-bismuth oxide composite oxide having a (111) crystal face as claimed in claim 8 in the preparation of formic acid by CO2 electroreduction.

10. The use according to claim 9, characterized in that: The potential for preparing formic acid by electroreduction is -0.8~-1.4.

Citation Information

Patent Citations

  • Solvothermal preparation method of bismuth trioxide microspheres and application thereof

    CN103420414A

  • Multivariate controllable synthesis method of BiOCl photocatalyst

    CN104014352A

  • Ag nanoparticle loaded amorphous bismuth oxide hollow core-shell nanosphere heterostructure material as well as preparation method and application thereof

    CN118957665A